1988
DOI: 10.1128/jvi.62.1.132-138.1988
|View full text |Cite
|
Sign up to set email alerts
|

Molecular comparisons of in vivo- and in vitro-derived strains of Aleutian disease of mink parvovirus

Abstract: DNA from one cell culture-adapted and two pathogenic strains of Aleutian disease of mink parvovirus (ADV) was molecularly cloned into the vectors pUC18 and pUC19. The DNA from the two pathogenic strains (ADV-Utah I and ADV-Pullman) was obtained from virus purified directly from the organs of infected mink, whereas the DNA from the nonpathogenic ADV-G was derived from cell culture material. The cloned segment from all three viruses represented a 3.55-kilobase-pair BamHI (15 map units) to Hindlll (88 map units) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…The experiments indicated that a determinant governing the ability of ADV to replicate in CRFK cells mapped to a 531-bp EcoRI-EcoRV fragment spanning nt 2553 to 3084 (Fig. 1) (12,14,15). No construction containing this MU 54 to 65 piece from ADV-Utah 1 was replication competent in CRFK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments indicated that a determinant governing the ability of ADV to replicate in CRFK cells mapped to a 531-bp EcoRI-EcoRV fragment spanning nt 2553 to 3084 (Fig. 1) (12,14,15). No construction containing this MU 54 to 65 piece from ADV-Utah 1 was replication competent in CRFK cells.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE and immunoblot analysis. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotting for ADV proteins were performed as detailed in previous publications (1,15,21,53), but the signal was developed with a chemiluminescent substrate (ECL; Amersham, Chicago, Ill.). This method amplified the sensitivity by at least a factor of 10 over standard chromogenic substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were incubated with a 1/100 dilution of ADVinfected adult mink serum and with a 1/4,000 dilution of peroxidase-labeled protein A (Boehringer Mannheim Biochemicals, Indianapolis, Ind.) and developed as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
“…Newborn mink kits were inoculated with 106 adult mink 50% infective doses and killed 10 to 20 days later. Virions were partly purified from lung, liver, and spleen tissues from the mink kits by isopycnic centrifugation in CsCl gradients, and DNA was extracted by the sodium dodecyl sulfate-proteinase K procedure (4,14).…”
Section: Methodsmentioning
confidence: 99%